Cu2ZnSnS4 solar cells with a single spin‐coated absorber layer prepared via a simple sol–gel route. (24th November 2015) - Youn, Na Kyoung; Agawane, Ganesh L.; Nam, Dahyun; Gwak, Jihye; Shin, Seung Wook; Kim, Jin Hyeok; Yun, Jae Ho; Ahn, SeJin; Cho, Ara; Eo, Young Ju; Ahn, Seung Kyu; Cheong, Hyeonsik; et al.
Summary: Carbon‐free Cu2 ZnSnS4 (CZTS) thin films were prepared via a simple spin‐coating process based on a sol–gel precursor of methoxyethanol solution with metal salts and thiourea, followed by post‐sulfurization. The sol–gel precursor solution was deposited onto molybdenum‐coated glass substrates. The sulfurization process was carried out using a conventional furnace at 525 °C for 60 min in a nitrogen atmosphere with sulfur powder. The structural, morphological and compositional properties of as‐sulfurized thin films were characterized using X‐ray diffraction, Raman spectroscopy, scanning electron microscopy and Auger electron spectroscopy. Only a single coating of the precursor solution was applied to obtain uniform Zn‐rich and Cu‐poor CZTS films thicker than 1 µm after post‐annealing. The best solar cell fabricated with the as‐prepared CZTS films of band gap energy ~1.37 eV showed a short‐circuit current density of 10.15 mA/cm 2, an open circuit voltage of 0.509 V, a fill factor of 33.72% and a conversion efficiency of 1.74%. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Nearly carbon‐free Cu2 ZnSnS4 (CZTS) absorber layers were prepared via sulfurization of single spin‐coated thin films deposited using a facile sol–gel technique. The best solar cell fabricated with a uniform CZTS absorber layer produced a conversion efficiency of 1.74% despite a porous microstructure of the absorber layer as well as the existence of several secondary phases, such as Cu2 SnS3 and ZnS. Further research on CZTS grain growth without secondary phases by optimizing the post‐annealing process will improve the photovoltaic cell performance.